2011
DOI: 10.4236/nr.2011.21002
|View full text |Cite
|
Sign up to set email alerts
|

Application of Solar Energy for Recovery of Water from Atmospheric Air in Climatic Zones of Saudi Arabia

Abstract: In the present work, an investigation on the application of solar energy to heat a sandy bed impregnated with calcium chloride for recovery of water from atmospheric air is presented. The study also aimed at evaluating the effects of different parameters on the productivity of the system during regeneration. These parameters include system design characteristics and the climatic conditions. An experimental unit has been designed and installed for this purpose in climatic conditions of Taif area, Saudi Arabia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
27
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(27 citation statements)
references
References 19 publications
0
27
0
Order By: Relevance
“…It was found also that the system was more efficient when operating at AlHada region. This is due to the dew point is higher compared with the city of Taif [16].…”
Section: Introductionmentioning
confidence: 77%
“…It was found also that the system was more efficient when operating at AlHada region. This is due to the dew point is higher compared with the city of Taif [16].…”
Section: Introductionmentioning
confidence: 77%
“…Ji, Wang, and Li (2006) and Hamed, Aly, and Zeidan (2011) experimentally investigated the recovery of water from atmospheric air using the composite material MCM-41and a sandy bed impregnated with calcium chloride. It was found that 1.2 kg and 1.0 L/m 2 water can be produced.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is necessary to look for alternatives to supply freshwater without affecting the environment and with adequate conditions for human consumption or use in other activities. At a global level, various strategies have been presented to reduce water scarcity, specifically in the improvement of hydraulic distribution systems (storage, distribution, and irrigation systems), rainwater harvesting, seawater desalination technologies, water management, and atmospheric water harvesting [21][22][23][24][25][26][27][28][29]. From the latter, fog and dew are major sources of water for arid regions [30].…”
Section: Introductionmentioning
confidence: 99%
“…It is known that about 280 cubic miles of water evaporate or transpire daily into the atmosphere, and the amount of water in atmospheric air is about 14,000 km 3 compared to only about 1200 km 3 of fresh water on earth [41]. Devices that harvest water from the atmosphere are called atmospheric water generators (AWGs) and can be used successfully both in arid areas with low moisture content and in humid areas with high moisture content [22,42,43]. In this work, we present a feasibility study on the use of atmospheric water generators (AWGs) for harvesting atmospheric air water in the region of Matehuala, SLP.…”
Section: Introductionmentioning
confidence: 99%